Design of a novel single-phase in two-phase out matrix converter driving an induction motor - Boztas, Gullu; Sunter, Sedat; Aydogmus, Omur (Inst Engineering Technology-Iet, 2016)
In this study, a direct ac-ac matrix converter is proposed to control a single-phase induction motor having main and auxiliary stator windings. This type of motors is widely used in low-power industrial machines, home appliances and many applications where single-phase grid is used. However, they require almost 90 degrees phase shift between the windings to obtain self-starting and high starting torque by using starting capacitor, centrifuge switch and auxiliary winding. These requirements can be met by the proposed converter which generates two-phase output voltages with 90 degrees phase shift and adjustable amplitude/frequency. The proposed converter can eliminate some disadvantages of inverter-based drive systems which require a bulky dc-link capacitor and a rectifier circuit. Also, regenerative operation, which is an important feature for electric motors, can be provided with the proposed converter structure. The converter has been tested with an R-L load and a standard single-phase induction motor with two-phase winding. Simulation and experimental results of the output voltages and load currents for the proposed drive system have been given for various output conditions. The performance of the motor has been also demonstrated for various speeds.
Keywords: Drives